The impact of illness perception on self-transcendence in gastric cancer patients undergoing chemotherapy: the chain mediating effect of hope levels and coping styles - Wang, Qin; Ren, Guoqin; Sun, Li; Zhang, Xumiao; Hua, Hongxia; Gu, Yanglin; Qu, Su (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the current status of illness perception, hope levels, coping styles, and self-transcendence among gastric cancer patients undergoing chemotherapy, and to explore the chain-mediating role of hope levels and coping styles in illness perception and self-transcendence.MethodsThis study is a cross-sectional study. A convenience sampling method was used to select 507 gastric cancer patients undergoing chemotherapy from a tertiary hospital in Wuxi City, China, from October 2024 to May 2025. A questionnaire survey was conducted using Demographic Characteristics Questionnaire, Brief Illness Perception Questionnaire, Herth Hope Index, Medical Coping Modes Questionnaire, and Self-Transcendence Scale. Data were analyzed by SPSS 27.0, R Studio and Amos 24.0.ResultsThe mean scores for illness perception, hope levels, confrontation, avoidance, yield and self-transcendence were 42.79 ± 9.30, 34.10 ± 9.21, 24.50 ± 9.51, 20.69 ± 6.30, 14.70 ± 4.61 and 44.08 ± 10.38, respectively. The importance ranking of the random forest model was: illness perception, avoidance, confrontation, hope levels, self-rated health status and yield. The mediation model analysis indicated that illness perception had a significant direct effect on self-transcendence (confrontation, avoidance, and yield dimensions: 55.47%, 56.04%, 53.73%), the independent mediating effect of hope levels (30.90%, 32.13%, 32.05%), the independent mediating effect of coping styles (6.81%, 6.28%, 7.95%), and the chain mediating effect of hope levels and coping styles (6.81%, 5.85%, 6.27%).ConclusionIllness perception directly influences self-transcendence in gastric cancer patients undergoing chemotherapy, indirectly influences self-transcendence through the mediating effects of hope levels, coping styles, and the chain mediating effect of hope levels and coping styles.